Pengaruh Terapi Murrotal Al-Qur’an Terhadap Kelancaran Produksi ASI Pada Ibu Postpartum Di PMB Anisa Mauliddina Sleman Yogyakarta - Khairiyah, Annisa Adzakiyyatul; Rosida, Luluk; Hapsari Listyaningrung, Tri (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Breast milk (ASI) is an emulsion of fat in a solution of proteins, lactose, and inorganic salts secreted by the mammary glands, serving as the primary source of nutrition for infants. According to the World Health Organization (2023), the exclusive breastfeeding rate in Indonesia was recorded at 67.96% in 2022, a decline from 69.7% in 2021. In Sleman Regency, out of 10,763 live births, only 57.89% of infants received exclusive breastfeeding for six months, while 42.11% did not. This indicates the need for more intensive support to improve exclusive breastfeeding coverage. One potential method to enhance breast milk production is through Murrotal Al-Qur’an therapy. Listening to Murrotal Al-Qur’an can help reduce stress, create a sense of comfort, relaxation, and calmness, which, in turn, significantly boosts breast milk production in nursing mothers. Objective of the study was to investigate the effect of Murrotal Al-Qur’an therapy on the smooth production of breast milk in postpartum mothers. This study employed pre-experimental design with one- group pretest-posttest approach. A total of 17 respondents were given a specific intervention, and observations were conducted before and after the treatment. Bivariate analysis was performed using the Wilcoxon test. Based on the bivariate analysis using the Wilcoxon test, there was a significant difference in breast milk production before and after the administration of Murrotal Al-Qur’an therapy. The statistical analysis yielded a p-value of 0.001. Conclusion was Murrotal Al-Qur’an therapy has a significant effect on improving breast milk production in postpartum mothers at PMB (Independent Midwife Practice) Anisa Mauliddina, Sleman, Yogyakarta.